Effect of ubiquinol on cardiorespiratory fitness during high-altitude acclimatization and de-acclimatization in healthy adults: the Shigatse CARdiorespiratory fitness study design - Yang, Jie; Ye, Xiaowei; Liu, Zhen; Sun, Mengjia; Yu, Shiyong; Lv, Hailin; Wu, Boji; Zhang, Chen; Gu, Wenzhu; He, Jingyu; Wang, Xuhong; Huang, Lan (Frontiers in Cardiovascular Medicine, 2023)
Cardiorespiratory function influences exercise capacity and is an important determinant of highaltitude adaptation. Some studies have investigated the characteristics of changes in cardiorespiratory fitness during high-altitude acclimatization. However, studies on changes in cardiorespiratory fitness during high-altitude de-acclimatization are still lacking and have not yet been elucidated. Furthermore, few drugs have been studied to improve cardiorespiratory function during both processes. The Shigatse CARdiorespiratory Fitness (SCARF) study is a single-center, randomized, double-blind, placebo-control clinical trial to explore the effects of ubiquinol on cardiorespiratory fitness during high-altitude acclimatization and de-acclimatization in healthy adults. Participants will be randomly assigned 1:1 to ubiquinol 200 mg daily or a placebo for 14 days before departure until the end of data collection after return in 7 days. Cardiorespiratory fitness is the primary outcome, while acute mountain sickness and high-altitude de-acclimatization symptoms are secondary endpoints. In addition, laboratory measurements, including routine blood tests and serological measurements, will be performed. To the best of our knowledge, the SCARF study will be the first to reveal the changes in the cardiorespiratory fitness characteristics during high-altitude acclimatization and de-acclimatization. Furthermore, the results of this study will contribute to exploring whether ubiquinol supplementation could be beneficial for endurance exercise capacity at different altitudes and help improve adaptation to acute hypoxia and de-acclimatization.Trial registration: This study has been registered in the Chinese Clinical Trial Register (www.chictr.org.cn) as ChiCTR2200059900 and ChiCTR2200066328.